The battle for Britain: MPs’ use of Facebook during the EU referendum campaign - Bon, Esmeralda Valentine (2021)
This is the age of the permanent campaign and professionalised political communication. Politicians must deliver and perform on a day-to-day basis. This includes UK members of Parliament. Notorious for taking their time in adopting digital means of communicating with their constituencies, especially in the 2000s, the majority can now be found both offline and online. This thesis presents an investigation into the online communication of politicians on Facebook about the EU referendum. The referendum provides a clear-cut context with two opposing camps in which differences and similarities in communication and campaigning between MPs, if any, come to light. This thesis consists of 6 chapters. In Chapter 1, I introduce this research, and in Chapter 2, I outline the method used for analysing and collecting the data, which is unique to this project. I thereafter present three empirical papers in Chapters 3-5. These papers each revolve around the study of MP communication at the time of the EU referendum campaign, using a novel data set of MP Facebook posts, published between February 19 and June 23, 2016. In the first empirical chapter (Chapter 3), I examine the active involvement of MPs in the EU referendum, on the Facebook platform, considering MP characteristics and using the corpus of relevant posts. Thereafter, in Chapter 4, I study how MPs communicate in these relevant posts, focusing on their use of emotion and argument. This is followed by the last empirical paper, in which I use time series analysis to investigate the dynamics of the EU referendum campaign of MPs on Facebook, to gain an understanding of the patterns in the prominence of campaign communication on this platform (Chapter 5). In the final chapter of this thesis, Chapter 6, I provide a conclusion.